The secret journeys of Jack London - Golden, Christopher; Lebbon, Tim 1969- (Harper / HarperCollins, 2011)
Seventeen-year-old Jack London makes the arduous journey to the Yukon's gold fields in 1893, becoming increasingly uneasy about supernatural forces in the wilderness that seem to have taken a special interest in him
Keywords: London, Jack / 1876-1916 / Juvenile fiction; London, Jack / 1876-1916 / Fiction; Geschichte 1800-1900; Adventure and adventurers / Fiction; Supernatural / Fiction; Survival / Fiction; Wolves / Fiction; Gold mines and mining / Fiction; Geschichte; Yukon / History / 19th century / Fiction; Canada / History / 1867-1914 / Fiction; Kanada